Sweden : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In Sweden, the authorities have indicated that their medium-term fiscal strategy is based on restraining expenditures through nominal ceilings and maintaining a fiscal surplus target of 2 percent of gross domestic product (GDP), measured as an average over the cycle. The mission has praised the authorities' medium-term fiscal strategy but argued that assuming that a structural surplus of 2 percent is maintained and that policy slippages on expenditures are avoided, the room for tax cuts is about 4 percent of GDP over the 2001-03 period, considerably more than envisaged by the authorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet